2018
DOI: 10.3389/fgene.2018.00609
|View full text |Cite
|
Sign up to set email alerts
|

Where to Cross Over? Defining Crossover Sites in Plants

Abstract: It is believed that recombination in meiosis serves to reshuffle genetic material from both parents to increase genetic variation in the progeny. At the same time, the number of crossovers is usually kept at a very low level. As a consequence, many organisms need to make the best possible use from the one or two crossovers that occur per chromosome in meiosis. From this perspective, the decision of where to allocate rare crossover events becomes an important issue, especially in self-pollinating plant species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 230 publications
(381 reference statements)
1
20
0
2
Order By: Relevance
“…DNA methylation is known to be important in modulating recombination rates in the model plant A. thaliana , which is realized in a strong anticorrelation between recombination rates and DNA methylation (Yelina et al , ; Zhao et al , ; Choi et al , ; Dluzewska et al , ; Tock and Henderson, ; Underwood et al , ). In line with that, we found that recombination rate and the level of DNA methylation were significantly anticorrelated, both in M. polymorpha and P. patens .…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is known to be important in modulating recombination rates in the model plant A. thaliana , which is realized in a strong anticorrelation between recombination rates and DNA methylation (Yelina et al , ; Zhao et al , ; Choi et al , ; Dluzewska et al , ; Tock and Henderson, ; Underwood et al , ). In line with that, we found that recombination rate and the level of DNA methylation were significantly anticorrelated, both in M. polymorpha and P. patens .…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of gametic COs is also known to be affected by variation in heterozygosity, with localised recombination frequency being dependent on factors including chromatin structure and repair mechanisms 54 . Recombination suppression may also be observed as a result of a heterozygous state in cis, with varying homolog polymorphism shaping meiotic recombination [67][68][69] . Heterozygosity is reportedly high in macadamia cultivars and wild accessions 22,[70][71][72][73][74] .…”
Section: Crossover Frequency and Recombination Varied Between Maps Dmentioning
confidence: 99%
“…Consequently, at any given location in the genome, there is general correspondence between the frequency of DSBs and the frequency of recombinants. In many, diverse taxa (e.g., fungi, plants, vertebrates), the DSBs and recombination events cluster at "hotspots" that regulate the frequency and distribution of recombination across the genome (4)(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%